Overview of Public Knowledge About Prevention of Acute Respiratory Infection in Work Area of Mandala Public Health Center Medan - Sulistiasari, Refi; Sumedi, Agus; Efendi, Handi; Lubis, Marlina Elfa; Zaim Anshari (International Journal of Public Health Excellence (IJPHE), 2025)
Acute respiratory tract infection (ARI) is an infection of the upper or lower respiratory tract. Causes, tract that can cause mild to severe infections, which are influenced by environmental infections, factors and host factors. The World Health Organization (WHO) reported that ISPA is the Lungs fourth disease with the highest number of deaths in the world. WHO also stated that the Mortality rate due to ISPA reaches 40 per 100,000 deaths. Basic Health Research Report (Riskesdas) in 2018, the number of ISPA cases in Indonesia reached 1,017,290 cases. The five provinces in Indonesia with the highest ISPA cases are East Nusa Tenggara (41.70%), Papua (31.10%), Aceh (30.00%), West Nusa Tenggara (28.30%) and East Java (28.30%).This study aims to determine the description of public knowledge regarding the prevention of ISPA. The data used is a questionnaire. Univariate and bivariate analysis using the chi square statistical test. Chi square test obtained a P value of 0.021, namely (p <0.05) so that it can be stated that H0 is rejected while H1 is accepted which indicates that there is a significant relationship between the level of knowledge of respiratory tract infections and in the Spearman test, a sig correlation (2 tailed) of 0.006 was obtained, namely (p <0.05) which means that there is a significant correlation between the two variables being tested.